Elephant boy of Burma - Harry, Robert R. (Robert Reese); Kalmenoff, Matthew (New York : Random House, 1960)
Poo Ban has turned twelve and is now old enough to work for the Englishman with his elephant.
Keywords: Asiatic elephant -- Burma -- Juvenile fiction; Elephants -- Fiction; Burma -- Fiction